Assessment on level of service of subsidized bus in Kajang, Selangor, Malaysia - Mat Shukri, Nur Shazreena (2021)
Subsidized public transportation service is widely offered in many urban societies in order to minimize the use of resources and to alleviate traffic congestion. Selangor, with its proximity to the capital of Malaysia, is known to have massive traffic congestion, especially in Kajang which is in the top four (4) districts with the highest number of Average Daily Traffic (ADT). Thus, a free fare program, subsidized bus was introduced in order to reduce the dependency on private vehicles among people. Specifically in this study, the subsidized buses is used to identify the level of service provided by the local authorities as an initiative in reducing traffic congestion at Kajang. Mixed method approaches will be used in the study's methodology. The researcher employ the Level of Service (LOS) method to measure the operational performance of subsidized buses for qualitative purposes. In the meanwhile, the quantitative method employs a questionnaire-based approach to uncover factors that can influence the quality of subsidized bus service and passenger satisfaction through SERVQUAL dimensions. On the whole, the LOS for subsidized bus service in Kajang achieved LOS D (acceptable standard) based on the assessment from four (4) main aspects that are service frequency, service hours, passenger threshold and bus speed. Additionally, the service quality of subsidized bus was influenced by assurance dimension which had a significant impact in influencing other dimensions on the SERVQUAL too. These findings can be linked to the different types of categories of passengers who involved in this study. Researcher conduct studies that are representative of practically all age groups who used subsidized buses on a daily basis. The level of passenger satisfaction is also considered in the survey, with the result that all passengers rate the subsidized bus service as satisfied. Passengers, local authorities, and bus management must work together to guarantee that this effort is sustained and, as a result, traffic congestion in Kajang is reduced. In addition, this study is also a bonus to the government where they can draw inspiration from this study in the development and improvement of public transportation network in the future. In fact, the use of LOS and SERVQUAL can be used as a benchmark for academia or other body knowledge in studying the quality of services for public transportation. However, there are several constraints that may be encountered, as in this study, such as the on-board environment during data collection on the bus and peak-hour crash load. Nonetheless, it can be prevented when researcher take some preliminary measures. In short, local authorities and bus management companies should work together in improving the service quality of the subsidized buses in order to maximize the number of ridership in the future. To ensure that the subsidized bus services can operate for a longer period of time, improvements and monitoring must be done on a regular basis.